Associations between Emotional Distress, Sleep Changes, Decreased Tooth Brushing Frequency, Self-Reported Oral Ulcers and SARS-Cov-2 Infection during the First Wave of the COVID-19 Pandemic: A Global Survey - Folayan Morenike O; Abeldaño Zuniga Roberto Ariel; Ezechi Oliver C; Brown Brandon; Nguyen Annie L; Aly Nourhan M; Ellakany Passent; Idigbe Iifeoma E; Khan AbeedhaT; Lawal Folake Barakat; Jafer Mohammed; Gaffar Balgis; et al. (MDPI, 2022)
This study assessed the association between emotional distress, sleep changes, decreased frequency of tooth brushing, and self-reported oral ulcers, and the association between COVID-19 status and decreased frequency of tooth brushing. Using a cross-sectional online survey, data were collected from adults in 152 countries between July and December 2020. Binary logistic regression analyses were conducted to determine the associations between dependent (decreased frequency of tooth brushing, oral ulcers, change in sleep pattern) and independent (tested positive for COVID-19, depression, anxiety, frustration/boredom, loneliness, anger, and grief/feeling of loss) variables after adjusting for confounders (age, sex, level of education, employment status). Of the 14,970 participants data analyzed, 1856 (12.4%) tested positive for COVID-19. Respondents who reported feeling depressed (AoR: 1.375), lonely (AoR: 1.185), angry (AoR: 1.299), and experienced sleep changes (AoR:1.466) had significantly higher odds of decreased tooth brushing frequency. Respondents who felt anxious (AoR: 1.255), angry (AoR: 1.510), grief/sense of loss (AoR: 1.236), and sleep changes (AoR: 1.262) had significantly higher odds of oral ulcers. Respondents who tested positive for COVID-19 had significantly higher odds of decreased tooth brushing frequency (AoR: 1.237) and oral ulcers (AoR: 2.780). These findings highlight that the relationship between emotional distress and oral health may intensify during a pandemic.